Empathy by default: correlates in the brain at rest - Silva, Patrícia Oliveira (2018)
Background: Empathy, defined as the ability to access and respond to the inner world of another person, is a multidimensional construct involving cognitive, emotional and self-regulatory mechanisms. Neuroimaging studies report that empathy recruits brain regions which are part of the social cognition network. Among the different resting state networks, the Default Mode Network (DMN) may be of particular interest for the study of empathy since it has been implicated in social cognition tasks. Method: The current study compared the cognitive and emotional empathy scores, as measured by the Interpersonal Reactivity Index, with the patterns of activation within the DMN, through the neuroimaging methodology of resting-state functional magnetic resonance. Results: Results suggest a significant positive correlation between cognitive empathy and activation of the bilateral superior medial frontal cortex nodes of the DMN. Contrastingly, a negative correlation was found between emotional empathy and the same brain region. Conclusions: Overall, this data highlights a critical role of the medial cortical regions of the DMN, specifically its anterior node, for both cognitive and emotional domains of the empathic process.